The digest2 NEO Classification Code. (19th April 2019) - Keys, Sonia; Vereš, Peter; Payne, Matthew J.; Holman, Matthew J.; Jedicke, Robert; Williams, Gareth V.; Spahr, Tim; Asher, David J.; Hergenrother, Carl
Abstract: We describe the digest 2 software package, a fast, short-arc orbit classifier for small solar system bodies. The digest 2 algorithm has been serving the community for more than 13 yr. The code provides a score, D 2, which represents a pseudo-probability that a tracklet belongs to a given solar system orbit type. digest 2 is primarily used as a classifier for Near-Earth Object (NEO) candidates, to identify those to be prioritized for follow-up observation. We describe the historical development of digest 2 and demonstrate its use on real and synthetic data. We find that digest 2 can accurately and precisely distinguish NEOs from non-NEOs. At the time of detection, 14% of NEO tracklets and 98.5% of non-NEOs tracklets have D 2 below the critical value of D 2 = 65.94 % of our simulated NEOs achieved the maximum D 2 = 100 % and 99.6% of NEOs achieved D 2 ≥ 65 at least once during the simulated 10-year timeframe. We demonstrate that D 2 varies as a function of time, rate of motion, magnitude and sky-plane location, and show that NEOs tend to have lower D 2 at low Solar elongations close to the ecliptic. We use our findings to recommend future development directions for the digest 2 code.